2006
DOI: 10.1159/000094137
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Wild-Type and a Mutated Form of SLC26A4 Identified in a Patient with Pendred Syndrome

Abstract: Background: Malfunction of the SLC26A4 protein leads to prelingual deafness often associated with mild thyroid dysfunction and goiter. It is assumed that SLC26A4 acts as a chloride/anion exchanger responsible for the iodide organification in the thyroid gland, and conditioning of the endolymphatic fluid in the inner ear. Methods: Chloride uptake studies were made using HEK293-Phoenix cells expressing human wild type SLC26A4 (pendrin) and a mutant (SLC26A4S28R) we recently described in a patient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 56 publications
6
50
0
Order By: Relevance
“…Consistent with a recent study (40), we found that niflumic acid, which can inhibit pendrin activity (37), only partially inhibited anion transport and mucus production induced by anion transporters including pendrin (Fig. 6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with a recent study (40), we found that niflumic acid, which can inhibit pendrin activity (37), only partially inhibited anion transport and mucus production induced by anion transporters including pendrin (Fig. 6).…”
Section: Discussionsupporting
confidence: 92%
“…Niflumic acid, a well-known blocker of anion transporters, has recently been shown to act as an inhibitor of pendrin (37). We thus investigated whether niflumic acid inhibits anion transport by pendrin, followed by attenuated mucus production (Fig.…”
Section: Effects Of Niflumic Acid On Mucus Production By Pendrinmentioning
confidence: 99%
“…In yet another study performed by Taylor et al (27) on PS/ns-EVA patients, three mutations of the same type (G672E, G102R, and Q446R) were described, and all showed a loss of functionality. We recently described a mutation, S28R, which again, reduced functionality (14,19). Another mutation, R409H, in which a Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…SLC26A4 Site-Directed Mutagenesis. The site-directed mutagenesis of SLC26A4 was done as described in detail in (14), and in SI Materials and Methods.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation